2014
DOI: 10.1007/s00228-013-1638-x
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate crushing information on ward lists: cytotoxic drugs, capsules, and modified release formulations are gravely neglected

Abstract: We found that the lists posted on the wards were often outdated and did not take into account the limitations/problems of preparing drugs on the ward. Our results emphasize that lists posted in wards need to be checked regularly and that "ready-to-use" lists from third parties might require adaptation to site-specific conditions in order to protect healthcare staff from exposure to potentially hazardous drugs during drug preparation and ensure safe drug application to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As the first intervention, we integrated a previously developed electronic database with information on crushing and suspending solid peroral drugs, the selection of proper solvents and – if necessary – safety standards (i.e. gloves, face masks) in the electronic drug information system of our hospital.…”
Section: Methodsmentioning
confidence: 99%
“…As the first intervention, we integrated a previously developed electronic database with information on crushing and suspending solid peroral drugs, the selection of proper solvents and – if necessary – safety standards (i.e. gloves, face masks) in the electronic drug information system of our hospital.…”
Section: Methodsmentioning
confidence: 99%
“…In order to avoid preventable manipulations, it is also important to provide the physicians and nurses with an overview of the available dosage forms and strengths appropriate for children. It has been shown that informational material regarding drug administration procedures on the wards is often outdated or not even available [ 17 ]. Therefore, integrating the information on drug dispensation and administration in paediatric wards as well as regular training should be part of each hospital quality management system.…”
Section: Discussionmentioning
confidence: 99%
“…They can affect dosing accuracy, bioavailability and integrity of the dosage form to an unknown extent. As a result, sub-therapeutic or toxic doses may be administered to vulnerable patient populations [ 12 , 15 , 16 , 17 ]. A randomised study in patients aged from 10–16 years showed that administration of crushed lopinavir/ritonavir tablets significantly reduced drug exposure compared to patients receiving whole tablets [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This type of administration error has also been reported in hospitals . Lists about the appropriateness of crushing or suspending oral dosage forms can be found on hospital wards, but the correctness of these lists has been found to vary 67.7%‐92.0% …”
Section: Discussionmentioning
confidence: 94%